Physical durability: are bed nets getting any stronger? - Amy Wheldrake; Estelle Guillemois; Hamidreza Arouni; Vera Chetty; Edoardo Zappa; Stephen J. Russell (Malaria Journal, 2024)
Abstract Background For at least a decade, concerns have been raised about the physical durability of insecticide-treated nets (ITNs) and their ability to remain in good condition for at least three years. To discover if the resistance to damage (RD) of ITNs has improved or not, the RD scores of ITNs sampled in 2013 and 2020 were compared. Methods The RD scores and disaggregated textile performance data for nine ITNs recommended by the WHO pesticide evaluation scheme (WHOPES) measured in 2013 were compared with WHO-prequalified ITNs sampled in 2020. This included assessment of newer ITNs not available in 2013, to determine the extent to which product development has led to performance improvements across all available ITNs in the intervening years. Results The resistance to damage of ITNs has not generally improved from 2013 to 2020, and in some cases performance is worse. The average RD score of comparable ITNs brands decreased from 40 in 2013 to 36 in 2020. Of the nets available in 2020, only two of the twenty-four ITN products tested achieved an RD score of > 50, while six ITNs had very low RD scores of < 30, highlighting a serious inherent, and literal weakness in many WHO-prequalified ITNs. Conclusions The long-term physical durability of ITN products cannot be expected to improve while their resistance to damage remains so low, and major upgrades to the performance standards of textile materials used to make ITNs, as well as incentives to develop stronger ones are urgently required.